Identifying the unauthorized user in e-government compliant system using valid proofs - T, Mekala; B, Devakar; P, Govindhasamy; Kanna B, Nishkal (International Journal of Engineering and Technology, 2018)
Citizens of our country face municipal complications like Street damage, Street cleaning, Garbage bin overflowing, light post damage, wa-ter outage etc. They started to register their complaints with advanced technologies. The complaint registration has many ways to file their complaints, it makes easier to register the complaint and saves our time. To solve these types of complications, we are going to implement a web application that helps the people to intimate about their issues directly to the government officer. So when the people iden-tify any complications in the city`s environment then, the government officer will solve the complications through his web portal. This will minimize time as well as money to go to an office for complaint registration. If the problem solved by those subjective then user will get the problem solved message. Otherwise, the problem will be again send to higher authorities to take action about it. The message alert will hap-pens repeatedly until the problem gets solve. Only the authorized persons have the rights to create the account by using aadhar card etc.Â
Keywords: Street Damage; Street Cleaning; Garbage Bin Overflowing; Light Post Damage; Water Outage and Traffic; Web Application; Message Alert; Web Portal.